Access to healthcare and social determinants of health among female migrant beggars in Ibadan, Nigeria - David Adewole; Bolaji Adedeji; Segun Bello; John Taiwo (Elsevier, 2023)
Introduction: Migration is a social determinant of health, and a major underlying factor of inequity of access to health and disparities in health outcomes. Migrant beggars from Northern part of Nigeria are a common feature in Southern Nigeria. Not too much is known about the challenges associated with access to healthcare and social determinants of health among this group of people in Nigeria. This study aims to fill existing gaps and contribute to the efforts of stakeholders in ameliorating the perennial challenges faced by this group of people. Materials and methods: The study was a descriptive cross-sectional study carried out among female migrants in the city of Ibadan. Using Open Data Kit (ODK), a semi-structured interviewer-administered questionnaire was used to collect data from respondents relating to access to health and basic social amenities, and challenges associated with these and as well as coping strategies. Data analysis was done with STATA version 15. More than a third-fifth of the respondents gave birth to their babies at home, used open defecation 189(49.6%), well/borehole 204(53.6%) is the source of drinking water. Three hundred and fifty-six (90.8%) of the respondents sleep in open space. Respondents with secondary school level of education, had a 129% increased odds of using health facilities compared to those who did not have any formal education (OR=2.29, p=0.014, CI: 1.18-4.44). Access to healthcare services and social amenities among women beggars was poor. There is a need for stakeholders to address this.